OPTIMIZATION OF THE ROLE OF TIKTOK SHOP AND PRODUCT INNOVATION IN THE DEVELOPMENT OF MSMES IN THE TEXTILE FIELD (CASE STUDY: PERNIAGAAN MARKET) MEDAN - Utari, Felicia; Irvan Rolyesh Situmorang (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Textile MSMEs, which are often small-scale with limited capital, produce a variety of products ranging from fabrics to clothing, with many relying on traditional crafts such as batik. On Jalan Perniagaan, Medan, textile MSMEs are the center of trade in fabrics and textile products, serving the needs of the community and business actors. The purpose of this study was to determine the optimization of the role of Tiktok Shop and product innovation in the development of MSMEs in the textile sector of the Medan Perniagaan market. In conducting this research, the researcher used a quantitative descriptive research method. The location of the research is on Jalan Perniagaan, Medan City. The research time is planned to take place from September 2024 to October 2024. The population used is all textile business actors on Jalan Perniagaan, where the number is 73 entrepreneurs. The sampling technique used is a saturated sample where the entire population is used as a research sample. The conclusion that researchers can draw from the results of this study is that partially and simultaneously there is an influence of Digital Marketing and Product Innovation on development in the Textile Sector of the Medan Perniagaan Market.